2022
DOI: 10.1155/2022/6753959
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of the Training of Aerobic Function on Clinical Symptoms and Quality of Life in Patients with Medium and Advanced Lung Cancer

Abstract: Objective. To investigate the effects of the training of aerobic function on clinical symptoms and quality of life in patients with medium and advanced lung cancer. Methods. The study objects were 84 patients with medium and advanced lung cancer who were treated in our hospital (July 2019–July 2021) and their materials were retrospectively reviewed. Depending on the different intervention modes, they were equally divided into control group (routine nursing intervention measures) and experiment group (training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…LUSC mostly occurs in elderly men who are addicted to smoking and is greatly affected by personal living habits [ 18 , 19 ]. Most patients have no significant symptoms in the early stage, or are accompanied by symptoms such as cough, bloody sputum, chest pain, and fever [ 20 ]. With the gradual deterioration of the disease will appear corresponding respiratory symptoms or cancer metastasis expansion.…”
Section: Discussionmentioning
confidence: 99%
“…LUSC mostly occurs in elderly men who are addicted to smoking and is greatly affected by personal living habits [ 18 , 19 ]. Most patients have no significant symptoms in the early stage, or are accompanied by symptoms such as cough, bloody sputum, chest pain, and fever [ 20 ]. With the gradual deterioration of the disease will appear corresponding respiratory symptoms or cancer metastasis expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, in patients with COVID-19, respiratory function is significantly affected during the acute phase, where ICU admission may occur. Previous studies showed that the pulmonary function of patients is compromised [18,28,29] and is marked by reduced lung capacity and volume and respiratory muscle weakness [18,30]; however, there are gradual improvements in FEV1 and FVC [18,[31][32][33], especially following interventions [34]. Hence, the lung functions of surviving patients with acute lung infections are expected to improve and may be normal in the majority of patients [35].…”
Section: Discussionmentioning
confidence: 99%
“…LC patients generally present with no obvious early symptoms, resulting in the fact that most of them are diagnosed in the middle and late stages with clinical presentations such as chest pain, hemoptysis, cough, and dyspnea [ 3 ]. Chemotherapy, a common treatment for patients with advanced LC, may also lead to adverse emotions such as irritability, depression, and cancer-related fatigue [ 4 , 5 ], all of which will not only exert varying degrees of negative effects on the self-efficacy and life quality of LC patients undergoing chemotherapy but also reduce patients' treatment compliance that lowers their treatment compliance [ 6 , 7 ]. This puts forward a demand for the management optimization of patients with LC chemotherapy, and exploring an effective and reliable high-quality nursing model is of positive significance for the rehabilitation of such patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%